Komunikasi Antarpribadi Pada Pernikahan Beda Usia - Ferawati Aulia Maharani; Siti Nursanti; Yanti Tayo (Jurnal Ilmiah Wahana Pendidikan, 2022)
Research on Communication Experiences in Age Difference Marriages (Phenomenological Studies in Age Difference Marriages) aims to determine the motives, meanings and experiences of communication in young marriages. This study uses the phenomenological theory of Alfred Scutz used to analyze the communication experiences of married women with their partners with large age differences. This study uses a qualitative method with a phenomenological approach. The results of the research and discussion show that there are differences in the meaning of marriage or marriage for a wife who is married at a different age, the difference in meaning occurs based on the experiences they experience, see and feel for themselves. Then the motive of a woman to marry, of course, the most important thing is to realize the ideal marriage according to each individual and be happy, even though there is a difference between reality and expectations. In the communication experience, of course, each informant has different experiences in his household.